Country Assessments: Identifying gaps in policy and practice to address equity in health for migrants. (13th November 2019) - Nordström, C; Ingleby, D; Dias, S; Magnus, J; Kumar, B
Abstract: Issue: The Joint Action on Health Equity in Europe (JAHEE) aims to address inequities in health across all groups. Work Package 7 Migration and Health (WP7) includes 13 partner countries and focuses on health inequities affecting the migrant population. The project started out by developing Policy Framework for Action (PFA), intended to form the basis for exploring opportunities for appropriate actions in the three-year implementation period of the action. The PFA formulated a 'road map' encompassing six priorities identified in 22 'soft policy' documents that have been published by international /governmental organisations since 2007. It also discussed the state of the art in research on the causes of particular inequities undermining migrant health, as well as the measures that can be taken to tackle them. Description of the problem: The main objective of the Country Assessments (CAs) is to identify the best opportunities (entry points) for developing country-specific actions. From this list, actions will be selected and implemented that are feasible within the constraints of JAHEE. The CAs will provide the information partners need in order to make informed choices. The assessments will indicate where the most serious inequities lie, what causes them, and what can be done about them. The CA Template was based on the PFA, reviewed by the Expert Group and then piloted in two countries (Norway and Italy) in March 2019. The 13 partners participating in WP7 are currently carrying out their assessments, which will be completed by July 2019. Results: An overview of the main results of the CAs will be presented at the conference. Lessons: Developing and piloting the Country Assessment Template has been participatory, with necessary revisions on the basis of experience. Completing these assessments for each participant is in itself is the first step towards action. Participants create an overview of available data, experiences and gaps in their countries. Key messages: The Country Assessment Template is a tool that enables partners to take stock of the situation in their country. Analysis of data from the assessments will enable countries to make an appropriate choice of actions.